ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA PERANGKAT DESA DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus di Desa Bercak, Desa Bercak Asri, Desa Kladi. Kecamatan Cermee Kab. Bondowoso) - Septianingrum, Rini; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2023)
The aim of this study was to analyze the factors of leadership style and work environment that influence the performance of village officials with Workout discipline as an intervening variable (case study in Bercak Village, Bercak Asri Village, Kladi Village, Cermee District, Bondowoso Regency). The sampling technique used in this research was a saturated sample with a total sample of 44 village officials. Data analysis and hypothesis testing in this research used Partial Least Square Structural Equation Modeling (PLS-SEM) The results of direct effect hypothesis test using Smart PLS 3.0 application showed that leadership style has a positive but not significant effect on work discipline, work environment has a positive but not significant effect on work discipline, leadership style has a positive but not significant effect on performance, work environment has a significant positive effect on performance, work discipline has a significant positive effect on performance, leadership style has nosignificant effect on performance through work discipline, work environment has not significant effect on performance through work discipline.